Right to the city in the age of neoliberal development: A case study of two slum communities in Dhaka, Bangladesh - Arefin, Shamsul (Society Register, 2023)
Due to rapid urbanization and the influence of neoliberal development policies, slum dwellers frequently encounter marginalization, inadequate living conditions, limited access to urban resources and spaces, and limited political representation throughout the world. Bangladesh is not an exception. This study investigates the right to appropriate and political participation of the urban poor in Bangladesh within the context of neoliberal development. In addition, the study critically evaluates the role of the state and various non-governmental organizations (NGOs) and civil society organizations in mobilizing the urban poor in Bangladesh. The study, therefore, implements a mixed-methods approach, including surveys, interviews, and community consultations, to obtain answers to these questions from two slums in Dhaka, Bangladesh, named Sattola and Pallabi. The findings show that the urban poor in these informal settlements confront significant challenges in claiming urban spaces due to local legislation, regulations, and development plans. As a result, they must negotiate with various formal and informal stakeholders to exercise their rights over urban spaces. The study also emphasizes that the urban poor face social and institutional barriers that limit their ability to participate effectively in decision-making, such as exclusion from formal political processes, limited access to information, and a lack of awareness of their rights. These difficulties exacerbate their marginalization from conventional urban development planning. Furthermore, the study demonstrates that due to the authoritarian state’s control over them, NGOs and other civil society organizations cannot assist the urban poor in mobilizing their right to the city. As a result, this study underlines the importance of a democratic government in Bangladesh for recognizing and defending the rights of the urban poor. Additionally, it emphasizes the importance of policy reforms and partnerships among government institutions, civil society organizations, and international actors to achieve inclusive and sustainable urban development that prioritizes the rights and well-being of the urban poor.